Profil gelatinisasi, karakteristik mikrobiologi dan sifat fungsional pati jagung ketan terfermentasi [Gelatinization profile, microbiological characteristics and funtional properties of fermented waxy corn starch] - Suryani Une; Rizky Killa; Lisna Ahmad; Zainudin Antuli; Husain Panggi (Jurnal Teknologi & Industri Hasil Pertanian, 2023)
Waxy corn (AJU1) is widely cultivated in Gorontalo Province, but its utilization is limited to corn on cobs.  A potential diversified product of processed waxy corn to be developed is waxy corn starch. One simple method to improve the functional properties of waxy corn starch is fermentation. This study aimed to determine the effect of different fermentation conditions and fermentation times on the gelatinization profile and functional properties of waxy  corn starch. The research method used a completely randomized factorial design with two treatment factors namely fermentation conditions (aerobic and anaerobic) and fermentation time (3, 6, and 9 days).  Results showed that the fermentation conditions significantly affected property of waxy corn starch.  During fermentation, there was a change in the number of cells of lactic acid bacteria, yeast, and mold. The gelatinization profile of  fermented waxy corn starch was to have resistant to stirring and high temperatures and reduced its retrogradation tendency. The fermentation process also changed the functional properties of glutinous corn starch, namely an increase in solubility, swelling, and acidity (decrease in pH).Keywords: aerobic, anaerobic, fermentation, starch, glutinous corn [AJU1]